Selection Analysis of Drive Chain Drive System of Diesel Engine Matching Valve Mechanism based on FEV Software - Shukun Wang; Yefeng Xu; Debing Yin; Xudong Zhao (Jixie chuandong)
The matching valve mechanism drive chain drive system is used to drive the matching valve mechanism of the engine, so that the engine intake and exhaust valves timely open and close, its selection results directly affecting the engine dynamic performance. The maximum working tension of a diesel engine chain is calculated theoretically on the basis of giving the relevant parameters of a diesel engine, and the primary selection of the chain is completed. Then, a matching valve mechanism driving chain transmission system is established in FEV software to input the required parameters in the early stage of simulation, and the maximum working tension of the chain is obtained through simulation. Then finish the chain final selection through the comparison of the two. The research results show that the selection method of the chain is reliable, it has been successfully applied in the selection of chain production enterprises.